2016
DOI: 10.1007/s00418-016-1422-y
|View full text |Cite
|
Sign up to set email alerts
|

Rab proteins in the brain and corpus allatum of Bombyx mori

Abstract: In eukaryotic cells, Rab guanosine triphosphate-ases serve as key regulators of membrane-trafficking events, such as exocytosis and endocytosis. Rab3, Rab6, and Rab27 control the regulatory secretory pathway of neuropeptides and neurotransmitters. The cDNAs of Rab3, Rab6, and Rab27 from B. mori were inserted into a plasmid, transformed into Escherichia coli, and then subsequently purified. We then produced antibodies against Rab3, Rab6, and Rab27 of Bombyx mori in rabbits and rats for use in western immunoblot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The Rab subfamily has also been related to neurodegenerative disorders such as Alzheimer’s disease and PD (Wilson et al, 2014; Saridaki et al, 2018; Yan et al, 2018). Previous studies have shown that Rab3A, Rab6, Rab8A/Rab8, Rab23, and Rab27b are highly expressed in the brain and participate in synaptic vesicle exocytosis, postsynaptic glutamate receptor dynamics, neurite growth and neural development (Takamori et al, 2006; Ng and Tang, 2008; Uno et al, 2016). Rab3 is the most abundant Rab protein in the brain.…”
Section: The Rab Subfamily In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
“…The Rab subfamily has also been related to neurodegenerative disorders such as Alzheimer’s disease and PD (Wilson et al, 2014; Saridaki et al, 2018; Yan et al, 2018). Previous studies have shown that Rab3A, Rab6, Rab8A/Rab8, Rab23, and Rab27b are highly expressed in the brain and participate in synaptic vesicle exocytosis, postsynaptic glutamate receptor dynamics, neurite growth and neural development (Takamori et al, 2006; Ng and Tang, 2008; Uno et al, 2016). Rab3 is the most abundant Rab protein in the brain.…”
Section: The Rab Subfamily In Non-neoplastic Cerebral Diseasesmentioning
confidence: 99%
“…Bombyxin, a member of the insulin family of peptides, is synthesized in the insect brain (Iwami, Furuya, & Kataoka, 1996;Mizoguchi et al, 1987;Nagasawa et al, 1986;Nagata et al, 1992) and is an essential growth factor for wing imaginal disks in Pseudodeltote coenia and M. sexta (Nijhout & Grunert, 2002;Nijhout et al, 2007). A previous report indicated that bombyxin-ir colocalized with Rab1-ir, Rab3-ir, Rab6-ir, Rab7-ir, and Rab14-ir (Uno et al, 2016). RabX4 may be involved in the synthesis, transport, and degradation of bombyxin in the brain of B. mori, in addition to other Rabs.…”
Section: Discussionmentioning
confidence: 99%
“…To clarify the relationship between Rabs and neuropeptide secretion, we performed anatomical and immunohistochemical analysis of the B. mori brain using antibodies against Rabs. Rab1, Rab3, Rab6, Rab7, and Rab14 have been previously shown to colocalize with bombyxin in the B. mori brain (Uno et al., ; Uno et al., ). Immunohistochemistry also revealed that Rab7 and Rab1 colocalized with eclosion hormone, while Rab1 colocalized with PTTH.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is also a lepidopteran model organism for genetic and immunology research (Liu, Ling, & Wu, 2009;Rao et al, 2016;Wang et al, 2017). In silkworms, the Rab protein mainly functions in the development of neurons (Uno et al, 2010(Uno et al, , 2013(Uno et al, , 2014(Uno et al, , 2016(Uno et al, , 2017. However, there is no report on the role of Rab in the innate immunity of the silkworm.…”
Section: Introductionmentioning
confidence: 99%